Orbital-Tripsy: Novel Combination of Orbital-Atherectomy and Intravascular-Lithotripsy, in Calcified Coronaries After Failed Intravascular-Lithotripsy - Chiang, Chi Shing Michael (JACC Case Rep, 2020)
Calcified coronary lesions are notorious for posing technical difficulty during angioplasty. Fortunately, more devices are available to tackle coronary calcifications. However, there remain difficult cases whereby a single modality is insufficient. Here we report the feasibility and success of a case, using Novo combination of Shockwave Lithotripsy after Orbital Atherectomy. (Level of Difficulty: Intermediate.)